The emerging potential of interactive virtual reality in drug discovery. (3rd July 2022) - Walters, Rebecca K.; Gale, Ella M.; Barnoud, Jonathan; Glowacki, David R.; Mulholland, Adrian J.
ABSTRACT: Introduction: The potential of virtual reality (VR) to contribute to drug design and development has been recognized for many years. A recent advance is to use VR not only to visualize and interact with molecules, but also to interact with molecular dynamics simulations 'on the fly' (interactive molecular dynamics in VR, IMD-VR), which is useful for flexible docking and examining binding processes and conformational changes. Areas Covered: The authors use the term 'interactive VR' to refer to software where interactivity is an inherent part of the user VR experience e.g . in making structural modifications or interacting with a physically rigorous molecular dynamics (MD) simulation, as opposed to using VR controllers to rotate and translate the molecule for enhanced visualization. Here, they describe these methods and their application to problems relevant to drug discovery, highlighting the possibilities that they offer in this arena. Expert opinion: The ease of viewing and manipulating molecular structures and dynamics, using accessible VR hardware, and the ability to modify structures on the fly ( e.g . adding or deleting atoms) – and for groups of researchers to work together in the same virtual environment – makes modern interactive VR a valuable tool to add to the armory of drug design and development methods.